MENINGKATKAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - REZKI, MAESTA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This scientific paper was motivated by the fact that Science (IPA) learning in classrooms has not yet achieved optimal results. Low academic scores and weak enthusiasm among students are the main challenges. One of the causes is the lecture-based teaching approach, which is